2015
DOI: 10.1155/2015/383279
|View full text |Cite
|
Sign up to set email alerts
|

Potential Environmental Benefits of Ultralight Particleboards with Biobased Foam Cores

Abstract: A new generation of ultralight particleboards (ULPB) with an expanded foam core layer produced in an in-line foaming step is under development. The environmental impacts of three types of ULPB containing foam based on 100% polylactic acid (PLA), 100% expanded polystyrene, and 50% PLA/50% polymethyl methacrylate, as well as a conventional particleboard (PB), have been compared in an LCA. Two approaches were chosen for the assessment: first, the “EPD-approach” in accordance with EN 15804 for EPD of building mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…dos Santos et al (2014) showed that the production of bagasse was the most relevant flow for eutrophication in an LCA of particle board due to the utilisation of fertilisers. The same observations were made by Ganne-Chédeville and Diederichs (2015) for the production of PLA contained in ultralight particle boards. Some crops need a high amount of water for irrigation.…”
Section: A1: Raw Materials Supplysupporting
confidence: 53%
See 3 more Smart Citations
“…dos Santos et al (2014) showed that the production of bagasse was the most relevant flow for eutrophication in an LCA of particle board due to the utilisation of fertilisers. The same observations were made by Ganne-Chédeville and Diederichs (2015) for the production of PLA contained in ultralight particle boards. Some crops need a high amount of water for irrigation.…”
Section: A1: Raw Materials Supplysupporting
confidence: 53%
“…The production of petrochemical, mainly synthetic binders and plastics (e.g. urea-formaldehyde, polyurethane, melamine, polyethylene, polyester or phenolic resins), is responsible for fossil resource depletion and often needs high amounts of input energy as fossil fuels, which lead to CO 2 emissions and contribute strongly to climate change (Rivela et al, 2005;Werner and Richter, 2007;González-García et al, 2009;Wilson, 2009;Silva et al, 2014;Sathre and González-García, 2014;Ganne-Chédeville and Diederichs, 2015). On the other side, bio-based additives, for example, tannin (Pizzi, 2008), corn starch, rubber, PLA (Ganne-Chédeville and Diederichs, 2015), sodium alginate (Palumbo, 2015), proteins, linseed oil or other natural extracts from plants and trees, can be used.…”
Section: A1: Raw Materials Supplymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce the environmental effects (substitution of petroleum raw materials), Yoon et al [46] proposed boards with polylactide foams, foamed with supercritical carbon dioxide. In addition, studies by Ganne-Chédeville and Diederichs [47] showed the benefits of replacing traditional particleboard materials with expanded polystyrene foam structures or polymethyl methacrylate or polylactide blends. The authors focused on environmental factors, including energy consumption during the production process.…”
Section: Introductionmentioning
confidence: 99%